Adaptive and highly accurate numerical treatment for a gradient‐enhanced brittle damage model. (29th March 2020) - Vogel, Andreas; Junker, Philipp
Summary: We present an adaptive numerical treatment for a recently published model for brittle damage with gradient enhancement. We employ adaptive strategies both in time and space, yielding detailed investigations of the convergence behavior: the damage distribution can be resolved with very high accuracy, turning the damage behavior into cracks known from fracture mechanics. Although the localization is extreme, mesh‐independent results are obtained thanks to the spatial adaptivity and allow for a detailed investigation of the influence of the regularization parameter.